2007
DOI: 10.1039/b709562g
|View full text |Cite
|
Sign up to set email alerts
|

Probing the reaction mechanism of aristolochene synthase with 12,13-difluorofarnesyl diphosphate

Abstract: 12,13-Difluorofarnesyl diphosphate, prepared using Suzuki-Miyaura chemistry, is a potent inhibitor of aristolochene synthase (AS), indicating that the initial cyclisation during AS catalysis generates germacryl cation in a concerted reaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
29
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 22 publications
3
29
0
Order By: Relevance
“…Section 1734 solely to indicate this fact. with the intact substrates FPP and 2-fluorofarnesyl diphosphate (2F-FPP) (12), and the inhibitor 12,13-difluorofarnesyl diphosphate (DF-FPP) (13). Differences observed in active site conformations and substrate conformations appear to be linked to differences in metal binding, analysis of which suggests a possible sequence for metal ion binding and conformational changes required for catalysis.…”
Section: Farnesyl Diphosphate (Fpp)mentioning
confidence: 99%
See 1 more Smart Citation
“…Section 1734 solely to indicate this fact. with the intact substrates FPP and 2-fluorofarnesyl diphosphate (2F-FPP) (12), and the inhibitor 12,13-difluorofarnesyl diphosphate (DF-FPP) (13). Differences observed in active site conformations and substrate conformations appear to be linked to differences in metal binding, analysis of which suggests a possible sequence for metal ion binding and conformational changes required for catalysis.…”
Section: Farnesyl Diphosphate (Fpp)mentioning
confidence: 99%
“…The syntheses of 2F-FPP and DF-FPP have been reported (12)(13)(14), and an additional synthesis of 2F-FPP is outlined in the supplemental materials. Recombinant A. terreus aristolochene synthase was expressed in Escherichia coli BL21(DE3)pLysS and purified as previously described (11,15).…”
Section: Enzyme Incubations With 2f-fpp and Df-fpp In Solution-mentioning
confidence: 99%
“…[5] Notably, Virgil and Corey demonstrated that lanosterol synthase could utilize vinyl ether 1 as a substrate in place of squalene oxide. [5a] In subsequent work by Jin and Coates, [5b] vinyl methyl ether-containing isoprenoid diphosphate 2 was used as a substrate for a diterpene synthase. This vinyl methyl ether, however, hydrolyzed rapidly in neutral aqueous conditions.…”
mentioning
confidence: 99%
“…,22 10 mM IPP, and 10 mM MgCl2 were incubated with 5 µM FPPS in 450 µL of 20 mM Tris buffer, pH 7.9, containing 500 mM NaCl overnight at RT, and the crude reaction mixture then stored at -20 °C.The thawed sample was filtered by centrifugation through an Amicon Ultra filter with 10 kDa molecular mass cutoff, and the flow-through fraction collected and lyophilized to dryness. After re-suspension of the lyophilized powder in 500 µL of D2O, and recording of a 1 H NMR spectrum, the presence of 3 vinyl protons matched a previously reported spectrum22 of 12,13-DFFPP and indicated that the enzymatic elongation of 8,9-DFGPP to 12,13-DFFPP had been successful. The sample was then lyophilized, re-suspended in 50 µL H2O, and stored at -20 °C until use.…”
mentioning
confidence: 99%